Estimation of base temperature in different growth stages of wheat Case study: Sararood Station of Kermanshah - yousof parsamehr; hosien mohammadi; faramarz khoshakhlagh; saied bazgeer (تحقیقات کاربردی علوم جغرافیایی)
In this study, in order to study the base temperature (minimum temperature for plant growth) at the degree of growth day (GDD), which is one of the important parameters in calculating the degree of growth day, first, the data required for the 2009-2017 statistical period of wheat production at the station Sararood was taken from the station. Then, after sorting and separating growth different stages, using four methods of calculating the base temperature (1 - minimum standard deviation SDgdd day, 2 - minimum standard deviation SDAY days, 3 - regression coefficient per day CRday, 4 - CV coefficient of variation) was the most suitable method for calculating the base temperature of growth in different stages of planting to wheat harvesting. The results showed that the most suitable method is the minimum standard deviation in GDD, which The base temperature was obtained from germination to full reach for different growth stages, 5/8, 0/38, 1/8, 2/6, 0/63, 2, 3/7, 9/7, 8/6, 11 degrees Celsius. By comparing different methods of calculating GDD, the most appropriate of method was the general method of calculating the degree of growth day due to the most of similarity to the station data. The degree of growth day in different stages was calculated based on their base temperature and the results showed that the calculation of the base temperature at each stage of the growth of the wheat was very accurate for GDD calculation and a precise estimate of GDD was obtained.